A Study of Students’ Perception on Using Facebook for Communication - Yohanes Mina, Yosua; Gatot Sutapa Yuliana, Yohanes; Riyanti, Dwi; Salam, Urai; Sumarni (Kirana Publisher (KNPub), 2023)
The research was aimed to find out students’ perception towards the use of Facebook for written communication outside of the classroom tenuously. The research was conducted in a descriptive quantitative study that was accomplished at the Eleventh grade students of Multimedia program major at SMK Negeri 6 Pontianak. The survey questionnaire was administered to the 50 participants throughout Google Form to collect the data accessibly. The result elucidated that the ground of Facebook had positively reinforced students (96%) to communicate in the English language within solitary and intercommunication state. Accordingly, the finding in the research presented that 80% of students agreed that Facebook is easy and pleasing to communicate in English autonomously. Further, 88% of students agreed that Facebook personal chat is the most used feature to communicate in English conveniently. Additionally, 66% of students agreed that Facebook allowed them to utilize English for written communication. In sum, the students were agreed on Facebook as a helpful platform for communication. It was shown in 50% students disagreed that they feel less embarrassed to communicate in English on Facebook as a challenge. Hence, students’ personal interest on Facebook can be channeled to communicate in English collaboratively. It is suggested that the use of Facebook for communication in English language considerably set the tool to encourage school integration of the educational technologically external environment.